The Aspergillus fumigatus maiA gene contributes to cell wall homeostasis and fungal virulence - Guruceaga, Xabier; Perez-Cuesta, Uxue; Martin-Vicente, Adela; Pelegri-Martinez, Eduardo; Thorn, Harrison I.; Cendon-Sanchez, Saioa; Xie, Jinhong; Nywening, Ashley V.; Ramirez-Garcia, Andoni; Fortwendel, Jarrod R.; Rementeria, Aitor (Frontiers in Cellular and Infection Microbiology, 2024)
In this study, two distinct in vitro infection models of Aspergillus fumigatus, using murine macrophages (RAW264.7) and human lung epithelial cells (A549), were employed to identify the genes important for fungal adaptation during infection. Transcriptomic analyses of co-incubated A. fumigatus uncovered 140 fungal genes up-regulated in common between both models that, when compared with a previously published in vivo transcriptomic study, allowed the identification of 13 genes consistently up-regulated in all three infection conditions. Among them, the maiA gene, responsible for a critical step in the L-phenylalanine degradation pathway, was identified. Disruption of maiA resulted in a mutant strain unable to complete the Phe degradation pathway, leading to an excessive production of pyomelanin when this amino acid served as the sole carbon source. Moreover, the disruption mutant exhibited noticeable cell wall abnormalities, with reduced levels of β-glucans within the cell wall but did not show lack of chitin or mannans. The maiA-1 mutant strain induced reduced inflammation in primary macrophages and displayed significantly lower virulence in a neutropenic mouse model of infection. This is the first study linking the A. fumigatus maiA gene to fungal cell wall homeostasis and virulence.